Browning of white adipose tissue uncouples glucose uptake from insulin signaling - Mössenböck, Karin; Vegiopoulos, Alexandros; Rose, Adam J.; Sijmonsma, Tjeerd P.; Herzig, Stephan; Schafmeier, Tobias (PLOS ONE, 2014)
Presence of thermogenically active adipose tissue in adult humans has been inversely associated with obesity and type 2 diabetes. While it had been shown that insulin is crucial for the development of classical brown fat, its role in development and function of inducible brown-in-white (brite) adipose tissue is less clear. Here we show that insulin deficiency impaired differentiation of brite adipocytes. However, adrenergic stimulation almost fully induced the thermogenic program under these settings. Although brite differentiation of adipocytes as well as browning of white adipose tissue entailed substantially elevated glucose uptake by adipose tissue, the capacity of insulin to stimulate glucose uptake surprisingly was not higher in the brite state. Notably, in line with the insulin-independent stimulation of glucose uptake, our data revealed that brite recruitment results in induction of solute carrier family 2 (GLUT-1) expression in adipocytes and inguinal WAT. These results for the first time demonstrate that insulin signaling is neither essential for brite recruitment, nor is it improved in cells or tissues upon browning.
Gesehen am 08.07.2020